2016
DOI: 10.15171/ijhpm.2016.32
|View full text |Cite
|
Sign up to set email alerts
|

An Implementation Research Approach to Evaluating Health Insurance Programs: Insights from India

Abstract: One of the distinguishing features of implementation research is the importance given to involve implementers in all aspects of research, and as users of research. We report on a recent implementation research effort in India, in which researchers worked together with program implementers from one of the longest serving government funded insurance schemes in India, the Rajiv Aarogyasri Scheme (RAS) in the state of undivided Andhra Pradesh, that covers around 70 million people. This paper aims to both inform on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…To facilitate management of policies across a ministry or department of health, the literature supported establishing consistent frameworks for M&E plans [ 11 , 21 , 29 , 33 , 41 , 57 , 60 , 68 , 72 , 74 , 83 , 85. , 86.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To facilitate management of policies across a ministry or department of health, the literature supported establishing consistent frameworks for M&E plans [ 11 , 21 , 29 , 33 , 41 , 57 , 60 , 68 , 72 , 74 , 83 , 85. , 86.…”
Section: Resultsmentioning
confidence: 99%
“…Sufficient education and training should be provided to implementers on policy details, and this training must be relevant to their role in policy implementation. [ 7 , 28 , 29 , 31 , 33 , 35 , 36 , 38 , 39 , 41 , 42 , 51 , 54 , 58 , 59 , 61 , 62 , 64 , 68 , 70 , 72 , 74 , 95 , 102. , 103.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is a need for a targeted approach toward the urban poor regarding health insurance. There is an urgent need for promoting technology support, product awareness, better pricing, and regulation of health insurance products (Bhat, Holtz, & Avila, 2018; Rao et al, 2016). Ayushman Bharath Pradhan Manthri Jan Arogya Yogna is a scheme with the objective of universal health coverage in India.…”
Section: Resultsmentioning
confidence: 99%
“…By definition, an implementation focus considers the nature of the programme, processes through which they are delivered, the role and responsibility of actors at different levels, and the context in which this occurs ( Damschroder et al ., 2009 ). Others have shown that an implementation focus results in substantively different research questions as compared with other approaches to programme improvement ( Rao et al ., 2016 ). Careful formulation of the research question(s) is needed to ensure results are relevant and actionable within the local reality for programme improvement.…”
Section: Discussionmentioning
confidence: 99%